The Effect of Product Quality, Online Customer Review and Flash Sale on Buyer Decisions Through E-Commerce as an Intervening Variable (Case Study of DKI Jakarta Students) - Rizki Hafrianzah Darim; Agustinus Miranda; Derriawan Derriawan (Sean Institute, 2024)
This research aims to determine the influence of the independent variable on the dependent variable through intervening variables. The population in this study were students from private universities in South Jakarta City using the lameshow formula, the sample in this study was 97 people. There are five types of variables in this research: Product Quality, Online Customer Reviews, Flash Sales, Buyer Decisions, E-Commerce. This research uses SEM Analysis and Smart PLS Application version 3.0 Partial Least Square (PLS) with a quantitative approach by distributing a questionnaire with 52 indicator statement items which can be seen from the AVE value of all variable values ​​> 0.5 so that overall there is a positive influence between variables.